SLO Guarantee and Cost Minimization under the Get Rate Variation in ES3 - Lavanya, Sankar (International Journal of Computer Sciences and Engineering, 2025)
Now a day’s each and everyone can store their data cloud because of its services and storage capacity. It is key for cloud advantage delegates to give a multi-appropriated restrain relationship to oblige their cost to cloud expert affiliations (CSPs) while giving service level objective (SLO) certification to their customers. Diverse multi-passed on restrict affiliations have been proposed or divide minimization or SLO guarantee. In existing system we simply store the data but we don’t know whether data will be secured or not that means we don’t have any guarantee on cloud providers still now only few works achieve both cost minimization and SLO guarantee. In this paper, we propose a multi-cloud Economical and SLO-ensured Storage Service (ES3), which picks information transport and asset reservation follows with fragment cost minimization and SLO ensure.ES3 joins an engineered data bit and resource reservation methodology, which assigns each data thing to a datacenter and determines the resource reservation amount on datacenters by leveraging all the pricing policies; (2) ) a genetic algorithm based data allocation adjustment method, which decrease data Get/Put rate contrast in each datacenter to enable the reservation to advantage. Our proposed system (i.e., Amazon S3, Windows Azure Storage and Google Cloud Storage) exhibit the unrivaled execution of ES3 in separate cost minimization and SLO guarantee in relationship with previous works.